An optimization of heuristic model of water supply network - Wyczólłkowski, Ryszard; Wysogląd, Bogdan (Computer Assisted Methods in Engineering and Science; Vol 14 No 4 (2007), 2022)
In the paper an intelligent monitoring system of local water supply system is described. The main task of this system concerns water leakages detecting. For inputs, this system uses information from few pressure or flow sensors, mounted on the pipeline network, the output is a piece of information about leakage detection and localization. A heuristic model of water supply network makes the main part of intelligent diagnostic system. The model was built with the use of artificial neural networks. This paper presents the structure and optimization of a heuristic model. The authors took advantage of methods of artificial intelligence and methods known from model-based process diagnostics to increase the accuracy with which system detects of water leakages.